2015
DOI: 10.1099/mic.0.000141
|View full text |Cite
|
Sign up to set email alerts
|

Unique and conserved genome regions in Vibrio harveyi and related species in comparison with the shrimp pathogen Vibrio harveyi CAIM 1792

Abstract: Vibrio harveyi CAIM 1792 is a marine bacterial strain that causes mortality in farmed shrimp in north-west Mexico, and the identification of virulence genes in this strain is important for understanding its pathogenicity. The aim of this work was to compare the V. harveyi CAIM 1792 genome with related genome sequences to determine their phylogenic relationship and explore unique regions in silico that differentiate this strain from other V. harveyi strains. Twenty-one newly sequenced genomes were compared in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…This example demonstrated the promise of SNP genotyping technology for analysis of genetic relationships in veterinary and environmental microorganisms. A comparison of genome regions in Vibrio harveyi and related species with the shrimp pathogen V. harveyi (CAIM 1792) demonstrated its higher similarity to those of other V. harveyi strains than to those of the other closely related species V. owensii, V. rotiferianus and V. campbellii (Espinoza-Valles et al, 2015). The SNP trees showed that V. harveyi is the most conserved of the four species studied, and V. campbellii may be divided into at least three subspecies.…”
Section: Resistance To Pathogensmentioning
confidence: 99%
“…This example demonstrated the promise of SNP genotyping technology for analysis of genetic relationships in veterinary and environmental microorganisms. A comparison of genome regions in Vibrio harveyi and related species with the shrimp pathogen V. harveyi (CAIM 1792) demonstrated its higher similarity to those of other V. harveyi strains than to those of the other closely related species V. owensii, V. rotiferianus and V. campbellii (Espinoza-Valles et al, 2015). The SNP trees showed that V. harveyi is the most conserved of the four species studied, and V. campbellii may be divided into at least three subspecies.…”
Section: Resistance To Pathogensmentioning
confidence: 99%
“…The presence of a pan-genome is associated with increased intra-species diversity, environment/host adaptations, and differentiations in pathogenic mechanisms (Tettelin et al, 2008 ). Several pan-genomic studies exist for different fish microorganisms, including marine pathogens such as Aeromonas salmonicida (Vincent and Charette, 2017 ), the Alteromonas ssp genus (López-Pérez and Rodriguez-Valera, 2016 ), and Vibrio harveyi (Espinoza-Valles et al, 2015 ). To define the entire core- and pan-genomes of an organism, a large quantity of fully sequenced genomes is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Such data have aided the study of phylogenomics 2 3 21 and the identification of diagnostic features in Vibrio species 22 . A recent study of V. harveyi compared the genome of this species with those of three other related ones 21 . Nevertheless, a detailed genomic analysis of the frequently misidentified pathogen V. campbellii is still absent.…”
mentioning
confidence: 99%
“…By applying genome-wide data, microbial taxonomy can be established via (1) average nucleotide identity (ANI) among sequences between two genomes 23 , and (2) the phylogeny of concatenated single copy orthologues, such as a core genome tree 2 21 . ANI ≥ 95% against type strains has become a commonly accepted definition of species 3 24 .…”
mentioning
confidence: 99%